Bilingualism for Dementia: Neurological Mechanisms Associated With Functional and Structural Changes in the Brain - Kim, Sujin; Jeon, Seong Gak; Nam, Yunkwon; Kim, Hyeon soo; Yoo, Doo-Han; Moon, Minho (Frontiers in Neuroscience, 2019)
As the number of older adults increases, the prevalence of dementias, such as Alzheimer's dementia (AD), Parkinson’s dementia, and vascular dementia, also increases. Despite research into pharmacological approaches for treating diverse diseases, there is still no cure. Recently, novel non-pharmacological interventions are attracting attention. Non-pharmacological approaches include cognitive stimulation, alterations in diet, physical activity, and social engagement. Cognitive stimulating activities protect against the negative effects of cognitive decline caused by age-related neurogenerative diseases. Bilingualism is one form of cognitive stimulation that requires multiple aspects of brain activity and has been shown to delay the onset of dementia symptoms in patients by approximately 4–5 years as compared with monolingual patients through cognitive reserve. The purpose of this review was to bilingualism protects against cognitive decline associated with AD and other dementias. We discuss potential underlying neurological mechanisms, including: 1) stimulating adult neurogenesis, 2) enhancing synaptogenesis, and 3) strengthening functional connectivity. that bilingualism may delay clinical AD symptoms by 4) protecting white matter integrity and 5) preserving gray matter density.